THREATS TO THE MANGROVES OF THANE CREEK AND ULHAS RIVER ESTUARY, INDIA. - MU. Borkar; G. Quadros; R.P. Athalye (JOURNAL OF COASTAL DEVELOPMENT, 2007)
The mangroves have adapted themselves best in the shallow sea coast, sheltered estuaries and deltaic:ones ofthe tropics and subtropics with characteristic environmental conditions vi:. temperature ranges between 200 C to 300 C, moderate to high monsoon precipitation i.e. [000 — 3000 mm/ annum, high humidity but with coastal aridity. On the sea-land intedace in global mangrove systems, there are gradual, slow or quickly changing ecological or geomorphological conditions to which mangroves have to adapt. The human thrust or pressure, other biotic factors and interactions also cause changes in mangrove ecosystems. Due to this the mangroves are now very dynamic but have become fragile through out the globe. Mangroves have various adaptations to cope with the stress to which they are subjected and jbr these adaptations they have to expend a lot of energy. Increased salinity has brought about floristic changes in the mangroves, particulariv in growth, form and structure of plant parts such as pneumatophores. thickening of leaves, salt extruding glands, viviparity stunted tree growth of some species and changes in plant communities. The mangrove forests stand as a barrier between the land and the sea and are jeeding and breeding grounds for dgferent fishery organisms. The mangroves if the world especiallv of the Indian continent are threatened and are on the verge of losing their identity. The study on the distribution of mangroves and the associate plants along Ulhas river estuary and the Thane creek during the period September 200] to August 2002 showed presence of 8 genera and I4 species ey' mangroves and I I genera and I2 species ry mangrove associates. The dominant mangrove type was Avicennia marina where as Acanthus ilicyblius was the mtyor associate type. When compared with the earlier data it was apparent that the mangrove cover was signtficantlv reduced The main threat to mangroves was due to anthropogenic activities, like cutting for jitel; reclamation for various purposes such as industry, agriculture, sand landing (reti-bunder), solid waste dumping, aquaculture ponds, construction of housing colonies, roads and bridges violating the CRZ regulation. There is an urgent need to conserve the mangroves of this region; which can be achieved through education, motivation of local people and strict supervision by administrative bodies and non-government organi:ations